Cancer-Associated Fibroblasts Modify the Response of Prostate Cancer Cells to Androgen and Anti-Androgens in Three-Dimensional Spheroid Culture - Eder, Theresa (Int J Mol Sci, 2016)
Androgen receptor (AR) targeting remains the gold standard treatment for advanced prostate cancer (PCa); however, treatment resistance remains a major clinical problem. To study the therapeutic effects of clinically used anti-androgens we characterized herein a tissue-mimetic three-dimensional (3D) in vitro model whereby PCa cells were cultured alone or with PCa-associated fibroblasts (CAFs). Notably, the ratio of PCa cells to CAFs significantly increased in time in favor of the tumor cells within the spheroids strongly mimicking PCa in vivo. Despite this loss of CAFs, the stromal cells, which were not sensitive to androgen and even stimulated by the anti-androgens, significantly influenced the sensitivity of PCa cells to androgen and to the anti-androgens bicalutamide and enzalutamide. In particular, DuCaP cells lost sensitivity to enzalutamide when co-cultured with CAFs. In LAPC4/CAF and LNCaP/CAF co-culture spheroids the impact of the CAFs was less pronounced. In addition, 3D spheroids exhibited a significant increase in E-cadherin and substantial expression of vimentin in co-culture spheroids, whereas AR levels remained unchanged or even decreased. In LNCaP/CAF spheroids we further found increased Akt signaling that could be inhibited by the phosphatidyl-inositol 3 kinase (PI3K) inhibitor LY294002, thereby overcoming the anti-androgen resistance of the spheroids. Our data show that CAFs influence drug response of PCa cells with varying impact and further suggest this spheroid model is a valuable in vitro drug testing tool.